Improved citation status of World Journal Gastroenterology in 2004: Analysis of all reference citations by WJG and citations of WJG articles by other SCI journals during 1998-2004 - Ma, Lian-Sheng (Baishideng Publishing Group Inc, 2005)
AIM: To determine the citation status in 2004 and the citation trend of WJG by analyzing all articles cited by WJG and all WJG articles cited by SCI journals during 1998-2004. METHODS: The total number of published articles and reference citations in WJG, authors’ self-citations, WJG’ self-citations, citations of WJG articles by SCI journals and inappropriate citations in WJG during 1998-2004 were statistically analyzed. Data on self-citations of the articles published between 1998 and August 2004 (Issues 1-16) were from ISI SCI-E, and data on self-citations of articles published after August 2004 (Issues 17-24) were from the WJG Editorial Office. Data on citations of WJG articles by other journals between 1998 and August 2004 were from ISI SCI-E. RESULTS: Annual number of published articles: WJG published 179, 144, 211, 174, 236, 634 and 830 articles, respectively, in 1998, 1999, 2000, 2001, 2002, 2003 and 2004. The number in 2004 increased by 594, compared to that in 2002, giving an increased rate of 251.7%. Annual references cited by WJG were 2 123, 2 125, 6 244, 8 883, 11 442, 23 218 and 25 971, respectively, in 1998-2004. The average number was 31.3 per WJG article in 2004, which was less than that (48.5) in 2002, giving a reduction rate of 35.5%. Authors of WJG cited 125, 126, 343, 210, 354, 310 and 470 of their own published articles, respectively, in 1998-2004. The average number of authors’ self-citations was 0.57 per WJG article in 2004, which was decreased by 0.93 or 62.0%, compared with that in 2002. Annual numbers of journal’ self-citations: Authors of WJG articles cited 5, 7, 373, 733, 1474, 1947 and 1412 of WJG articles, respectively, in 1998-2004. The average number of journal’ self-citations was 1.70 per WJG article in 2004, which decreased by 4.55 or 72.8%. No WJG article was cited in 1998 by other SCI journals. However, the number of citations steadily increased afterwards, with 16, 18, 39, 85, 372 and 580, respectively, in 1999-2004. The average number of citations by other SCI journals was 0.11, 0.09, 0.22, 0.36, 0.59 and 1.06 per WJG article, respectively, 1999-2004 (January-August). There was an increase by 582%, when comparing the citation numbers between 2004 and 2002. Annual WJG self-citation rates and citation rates of WJG articles by other SCI journals: WJG self-citation rates were 30.43%, 95.40%, 95.07%, 94.55%, 83.96% and 67.47%, respectively, in 1999-2004 (January-August). Compared with 2002, the self-citation rate in 2004 decreased by 26.87%. The citation rates of WJG articles by other SCI journals were 69.57%, 4.60%, 4.93%, 5.45%, 16.04%, and 32.53%, respectively, in 1999-2004 (January-August). Compared with 2002, the citation rate in 2004 decreased by 26.87%. There were 8, 19, 218, 274, 461, 698 and 574 inappropriate citations, respectively, in 1998-2004. The average inappropriate citation in 2004 was 0.69 per article, which represents a decrease of 1.26, compared with that in 2002. Inappropriate citations were mostly those with the differences between the two sides of the hyphens of 5-9, and the proportions of inappropriate citations within the three subsections of the differences between the two sides of the hyphens (5-9, 10-19, and >=20) were approximately 7:2:1. In addition, inappropriate citations mostly occurred with frequencies of 1-3 in the articles, and the proportion of inappropriate citations within the two frequency subsections (1-3 and >3) have been approximately 4:1 since 1999. CONCLUSIONS: In 2004, the average number of reference citations, authors’ self-citations and journal’ self-citations were 31.3, 0.57 and 1.70 per article, respectively, which represents a decrease in the numbers by 35.5%. 62.0%, and 72.8% respectively compared to the corresponding numbers in 2002. WJG self-citation rate was 67.47% in 2004 (January-August), which was a decrease by 26.87%, compared with 2002. The citation rate of WJG articles by other SCI journals was 32.53% in 2004 (January-August), an increase of 26.87%, compared to 2002. There were 574 inappropriate citations in 2004, with an average of 0.69 per article, which represents a decrease of 1.26, compared with that in 2002. These figures demonstrate that the overall citation status of WJG is improving.